2019
DOI: 10.1016/j.bbmt.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation in Children and Adolescents with Acute Lymphoblastic Leukemia from a Matched Donor versus an HLA-Identical Sibling: Is the Outcome Comparable? Results from the International BFM ALL SCT 2007 Study

Abstract: Eligibility criteria for hematopoietic stem cell transplantation (HSCT) in acute lymphoblastic leukemia (ALL) vary according to disease characteristics, response to treatment, and type of available donor. As the risk profile of the patient worsens, a wider degree of HLA mismatching is considered acceptable. A total of 138 children and adolescents who underwent HSCT from HLA-identical sibling donors (MSDs) and 210 who underwent HSCT from matched donors (MDs) (median age, 9 years; 68% male) in 10 countries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…Bu/Cy/Eto was the second most frequently used MAC. This combination was applied in the international Berlin-Frankfurt-Münster (iBFM/ BFM) clinical trials [1,40,41], particularly in infants (Interfant-99) [42,43], and elsewhere [2,[44][45][46][47]. Within the observation period of this study, the alternative alkylator, treosulfan, was increasingly used for children with malignancies; but no treosulfan-containing regimen reached a significant number of cases [48].…”
Section: Discussionmentioning
confidence: 99%
“…Bu/Cy/Eto was the second most frequently used MAC. This combination was applied in the international Berlin-Frankfurt-Münster (iBFM/ BFM) clinical trials [1,40,41], particularly in infants (Interfant-99) [42,43], and elsewhere [2,[44][45][46][47]. Within the observation period of this study, the alternative alkylator, treosulfan, was increasingly used for children with malignancies; but no treosulfan-containing regimen reached a significant number of cases [48].…”
Section: Discussionmentioning
confidence: 99%
“…4-year EFS and CIR were also similar in both groups. NRM was lower in the MSD-group in the BFM-2003 study but appeared similar between MSD and MD-groups in the I-BFM-2007 [ 5 , 6 ]. Because of these published results, we decided to merge MSD and MD transplanted patient sub-groups for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, all these studies demonstrated the need for developing new approaches in order to increase the cure rate and to decrease the relapse incidence. Our algorithm of risk-group allocation was based on a combination of both biological and clinical criteria at time of disease occurrence and MRD level at the end of induction and of consolidation courses, in first and second line therapy [ 2 , 6 , 29 ]. Obtaining a better disease control before HSCT represents the absolute challenge we have to face [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25,27,40,41 Further intensification of chemotherapy to decrease or eliminate MRD and HSCT itself are not without significant risk of morbidity and mortality. 3,22,28,42 Therefore, the possibility of durable remission without consolidative HSCT is one aim of an ongoing trial developed by the COG and Novartis. AALL1721/Cassiopeia (Clinical Trials.gov identifier: NCT03876769), a phase 2 single-arm trial of tisagenlecleucel in children and young adults with National Cancer Institute HR B-ALL and persistent MRD at EOC, is the first trial of CAR T-cell therapy in CR1.…”
Section: Aall1721/cassiopeiamentioning
confidence: 99%